2016
DOI: 10.1007/s10103-016-2009-5
|View full text |Cite
|
Sign up to set email alerts
|

Low intensity laser and LED therapies associated with lateral decubitus position and flexion exercises of the lower limbs in patients with lumbar disk herniation: clinical randomized trial

Abstract: pain intensity assessed by visual analog scale (VAS), degree of flexion of the affected hip measured by the universal goniometer and functional capacity assessed by the Oswestry Disability Index. The three groups had statistically significant improvement in lumbar and radicular pain, in hip mobility, and in the functional disability index (p ≤ 0.001). There was a statistically significant difference (p = 0.024) in radicular pain between the groups, gait claudication and Oswestry Disability Index. We can conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Similar results were obtained by De Carvalho et al, 17 who compared the effectiveness of LLLT and sham interventions with a low-energy laser, as well as light-emitting diode (LED)-type polarized light irradiation. Patients, in addition to the 15 therapeutic applications, performed stretching exercises of the lower limbs.…”
Section: Discussionsupporting
confidence: 80%
“…Similar results were obtained by De Carvalho et al, 17 who compared the effectiveness of LLLT and sham interventions with a low-energy laser, as well as light-emitting diode (LED)-type polarized light irradiation. Patients, in addition to the 15 therapeutic applications, performed stretching exercises of the lower limbs.…”
Section: Discussionsupporting
confidence: 80%
“…A Brazilian RCT study (5) evaluated the effectiveness of LLT and LED radiation therapy associated with lateral decubitus position and exercises of the lower extremities in patients with lumbar hernia. A group of 54 subjects were assigned into groups: LLLT treatment using 904 nm (n=18), placebo LLLT (n=13), and LED treatment using 945 nm (n=18).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous scientific reports in the literature demonstrate the significant utility and clinical efficacy of laser therapy (14). Nevertheless, it should be noted that other more critical studies testify to the lack of purposefulness of laser radiation (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 ] Currently, few studies have investigated the use of bright light or LED therapy in Carvalho et al showed that LED therapy in lateral decubitus position and with flexion exercises of the lower limbs for the treatment of L4-L5 and L5S1 lumbar disk herniation with radiculopathy showed better therapeutic performance for radicular pain, gait claudication, and functional disability. [ 31 ] In addition, Hsieh and Lee showed that treatment with hot-pack therapy and 890-nm light therapy is associated with reductions in the severity of disability and fear avoidance beliefs in patients with CLBP. [ 32 ] The use of 890-nm light therapy was approved by the United States Food and Drug Administration for the treatment of minor muscle and joint pain in 2002.…”
Section: Introductionmentioning
confidence: 99%